Validity Of The Development Of Truth Or Dare Card Media For Teaching Negotiation Text Material In High School - Nur Afni Widari; Silvia Permatasari; Zulhafizh (Universitas Sulawesi Barat, 2025)
This study aims to describe the validity of the Truth or Dare card media in learning negotiation text material in high school. This research is a type of Research and Development (R&D) using the ADDIE model. In this study, several stages were carried out, namely: 1) Analysis, 2) Design, 3) Development. After the development stage was carried out, the media was validated by 3 validators, namely material, media, and language experts using an assessment instrument in the form of a validation sheet which then produced validation score data. The validation results showed that the Truth or Dare card media for learning negotiation text material in high school was worthy of being tested for use in learning by obtaining an average of 90% in the very valid category.